Fostering Meaningful Learning in Third Graders: Implications for Foreign Language Teaching (2024)
ABSTRACT: The goal of this study was to improve the acquisition and retention of English vocabulary among third-grade EFL students at IESA by integrating Ausubel's meaningful learning theory with challenge-based instruction. The study included qualitative techniques, such as student feedback, teacher journals, and classroom observations. The results showed that using interactive challenges and gestures greatly increased students' capacity to relate new words to what they already knew, which improved comprehension and retention. The study also pointed out that time restrictions made it difficult to completely execute the challenge-based strategy. Despite challenges, the experiences showed how this method may be used to generate chances for meaningful learning through involvement and active participation.